Perancangan User Experience Aplikasi Konsultasi Kesehatan Mental Online di Masa Pandemi berbasis Mobile menggunakan Metode Design Thinking - Fadhil Arif Muhammad; Agi Putra Kharisma; Riswan Septriayadi Sianturi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The COVID-19 pandemic is an epidemic that not only affects the physical condition, but also the mental condition of a person. For students in particular, the COVID-19 pandemic has an impact on student acceleration in experiencing a quarter-life crisis so that students become anxious, insecure, and stressed. Therefore, researchers designed a mobile application user experience to help the community, especially students with an age range of 18-25 years, to reduce the stress experienced by consulting online and offline experts. The method that the researcher uses in this research is Design thinking because this method focuses on the user experience so it is suitable for mental health consulting applications. For validation, usability testing was carried out on 10 respondents by getting the success rate effectiveness aspect value of 90.5%, efficiency aspect using Time Based Effieciency calculation of 0.078 goals/second, and satisfaction aspect by getting a score of 83.25 which classified as B, Excellent rating, and acceptable category. Furthermore, user experience testing was also carried out on 20 respondents using the User experience questionnaire (UEQ) questionnaire with the results of the attractiveness aspect of 2.16, the perspicuity aspect of 2.06, the efficiency aspect of 2.28, the dependability aspect of 2.15, the stimulation aspect of 2.08, and the novelty aspect. of 1.43. Then the test results become the basis for researchers to make improvements to the interface in accordance with the feedback given by the respondents.